Saúde íntima feminina e sensualidade nas lingeries - Brás, Luma de Jesus (2016)
Due to increasing competitiveness, companies often need to innovate frequently to stay active and well regarded in the market, even more when it comes to a product like lingerie, related mostly to the female audience considered consumerist and demanding public. For this reason, it is relevant product innovation, as well as their production processes to become increasingly competitive, staying in the market and gaining preference. Thus the aim of this paper is to present the creation of a collection of fashion oriented women's intimate health without unconfiguring fashion trends, taking into account the sensuality and comfort required by most women. The study consists of working with cotton fiber so that, if present as a product which triggers sensuality causing the search to focus on issues that relate the search for sensuality through lingerie, how was the transformation this segment throughout history aggregating research women's intimate health through the benefits of cotton fiber.